Using the triple proxy δ13C-radiocarbon-major and trace elements to understand stalagmite stable carbon composition in Madagascar - Voarintsoa, Ny Riavo G.; Therre, Steffen (Chemical geology, 2022)
Stalagmite δ13Cc is one of the most complicated and difficult proxies to interpret in paleoclimate and paleoenvironmental studies because of its sensitivity to various local, regional, and global factors. The significance of the large δ13Cc shift (~12‰, vs. VPDB) in several stalagmites from Anjohibe Cave, in northwestern Madagascar, in the late Holocene remains a subject of scientific debate. Although it was assumed to reflect C3 to C4 vegetation cover change caused by anthropogenic activities, recent investigations inside the cave, at different locations, revealed a wide δ13Cc range of ~10‰ (vs. VPDB), a value that is comparable in its significance to the 12 ‰ temporal variability mentioned above. In this paper we combine δ13C, radiocarbon (14C), and major and trace elements (MTE) as a proxy to provide additional insights about the non-vegetation drivers of δ13Cc in Madagascar. Our study uses two models, the CaveCalc model and the Fohlmeister model, to help our interpretation of the drip water evolution while it percolates down to the cave and precipitates CaCO3. The radiocarbon results, with values >100 pMC, demonstrate that the bomb peak, i.e., the pronounced increase in atmospheric 14C signals, are clearly recorded in these modern stalagmites. This suggests that the samples are younger than 1950 CE, and the soil carbon cycling has been fast without significant formation of aged soil organic matter. These radiocarbon results further suggests that stalagmites from Anjohibe Cave might be of use for future efforts to reconstruct past atmospheric 14C concentrations. Drip water geochemistry, δ13Cc and MTE, combined with two model simulations (CaveCalc and Fohlmeister model) suggests that the great δ13Cc range is best explained by the combined effects of the DIC residence time in the epikarst that affect the water-rock interaction and the rate of prior carbonate precipitation. This study therefore demonstrated how combined modelling and multi-proxy approaches can advance our understanding of the control mechanisms of δ13Cc for paleoclimate research.
Gesehen am 14.09.2022
Im Titel wird "delta" als griechischer Buchstabe dargestellt